AI, Task Changes in Jobs, and Worker Reallocation - Christina Gathmann; Felix Grimm; Erwin Winkler (Institute of Labor Economics (IZA), 2024)
How does Artificial Intelligence (AI) affect the task content of work, and how do workers adjust to the diffusion of AI in the economy? To answer these important questions, we combine novel patent-based measures of AI and robot exposure with individual survey data on tasks performed on the job and administrative data on worker careers. Like prior studies, we find that robots have reduced routine tasks. In sharp contrast, AI has reduced non-routine abstract tasks like information gathering and increased the demand for 'high-level' routine tasks like monitoring processes. These task shifts mainly occur within detailed occupations and become stronger over time. While displacement effects are small, workers have responded by switching jobs, often to less exposed industries. We also document that low-skilled workers suffer some wage losses, while high-skilled incumbent workers experience wage gains.
Keywords: J23; J24; J31; J62; 330; reallocation; skills; tasks; Artificial Intelligence; robots; patents